Numerical determination of plastic CTOD. Issue 10 (16th July 2018) - Antunes, F.V.; Díaz, F.A.; Vasco‐Olmo, J.M.; Prates, P.
Abstract: In previous works, a da/dN versus plastic crack tip opening displacement model was proposed to study fatigue crack growth. The plastic crack tip opening displacement, δp, which quantifies the crack tip plastic deformation, is determined numerically using the finite element method. The predictions are affected by different numerical parameters which must be identified and studied. The main parameters are the crack propagation distance, the distance of measurement points relatively to the crack tip, the size of crack tip elements, and the number of load cycles between crack increments. Some crack propagation is required for the stabilization of δp, which occurs when δp reaches its minimum value. The measurement point behind crack tip has a major effect on δp . The peak value occurs at the first node behind crack tip and a progressive decrease of sensitivity is observed with the increase of distance to crack tip. A mesh refinement study showed a coincidence of the predictions obtained with different meshes, which is a good indication for the robustness of the procedure. Finally, there is a significant effect of the number of load cycles between crack increments, NLC, in the presence of crack closure. The increase of NLC reduces the crack opening level and so increases δp .